ANALISIS KINERJA KEUANGAN SEBELUM DAN SETELAH PEMEKARAN DAERAH (STUDI KASUS KABUPATEN MANOKWARI, KABUPATEN MANOKWARI SELATAN, KABUPATEN PEGUNUNGAN ARFAK) - Kapitarauw, Glerisida; Alisyah, La Ode; Situmorang, Elina R. (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2025)
Analysis of Financial Performance Before and After Regional Expansion, case studies in Manokwari Regency, South Manokwari Regency and Arfak Mountains Regency. This research aims to determine the Financial Performance of the Expansion Region by analyzing the Financial Independence and Dependence of the Expansion Region. Analyzed using the Quantitative Descriptive method, the results of this research show that the Financial Performance Analysis before and after the expansion of Manokwari Regency, which consists of the Independence Ratio and Dependency Ratio, is classified as instructive and very high, which means that the analysis of financial performance before and after the expansion of the Manokwari Regency area is said to be not yet independent and still dependent on transfer funds from the central government. The results of the Regional Financial Performance Analysis of South Manokwari Regency and Arfak Mountains Regency after being separated from Manokwari Regency, consisting of an independence ratio and a dependency ratio show that they are not yet independent and still depend on income from transfer funds from the central government.